University Students' Acceptance of Evolution: Basis for STEM-based Instructional Design - Odessa D. Aberilla; Monera H. Salic; Ronaldo R. Orbita; Joy B. Bagaloyos; Cesar G. Demayo; Mark Anthony G. Torres (International Journal of STEM Education for Sustainability, 2021)
This study was conducted to explore the overall acceptance of evolution among undergraduate students in a State University as basis for developing a STEM-based instructional design to address the misconceptions about evolution. The research was conducted using the 20-item questionnaires of the Measurement of Acceptance of the Theory of Evolution (MATE) instrument assessing undergraduate students' acceptance of evolution in relations to; the process of evolution, the scientific validity of the evolutionary theory, the evolution of humans, evidence of evolution, scientific community's view of evolution and age of the Earth. The study is within a quantitative and qualitative framework using descriptive and inferential analysis. The findings revealed that all the colleges in the science group acquired a moderate level of acceptance except for the CED non-science group who received a low degree of acceptance of the theory of evolution. Although among the six concepts in the study, they generally agree on the statements and only in the idea on the age of the earth where the students were undecided. This research confirms that the level of acceptance is not positively related to the students' specialization. Based on the result of this study there is a need to develop a STEM based instructional design and this should be emphasized in the science curriculum. The teaching design will fill in the gaps in understanding concepts of evolution and its significance to the lives of many organisms and for the teachers to look evolution from very broad flexible and interdisciplinary perspectives.